DIAGNOSIS OF DIABETIC MACULAR EDEMA (DME) BASED ON FUNDUS FLUORESCEIN ANGIOGRAPHY (FFA) FINDINGS - Qamar Mehboob; Zafar Hussain; Muhammad Arif (Journal of University Medical & Dental College, 2015)
ABSTRACT: PURPOSE: The present study was designed to see the Physiological changes in diabetic macular edema (DME) as assessed by fundus Fluorescein angiography (FFA) and to plan the appropriate treatment regime for the patients after assessing the specific type of diabetic macular edema adopted internationally. STUDY DESIGN: Prospective observational study. The patients were selected by simple random technique. MATERIALS AND METHODS: Total one hundred patients (200 eyes) were selected according to the inclusion and exclusion criteria. They were examined in the outpatient department and diagnosed having as diabetic macular edema with no opacity in refractive media. After checking their visual acuity (VA), FFA was done in the Diagnostic and Research Centre, Department of Ophthalmology, Allied hospital, Faisalabad. Pakistan. The data was collected, arranged and analyzed. DURATION; Jan 2012 – Jan 2013 RESULTS: Out of 200 eyes, on FFA our results showed diffuse maculopathy in 140 eyes (70%), Focal type in 36 eyes (18%) and Ischemic type in 24 eyes (12%). CONCLUSION: The treatment schedule of all types of diabetic macular edema highly differs with each expert other. So, for proper diagnosis and treatment is concerned only clinical examination cannot be relied upon